Asia-Europe young artists' painting competition : The new millenium in my dreams organised by Asia-Europe Foundation. - Oh, Jay-Hee; Koh, Tommy; Leong, Ho Kah; Rongsheng, Cai; Sang, Park Kwon; Lim, CP; ASEM III, Seoul (Seoul : Asia-Europe Foundation, 2000)
Zhenghua, Ye ; Mendoza, Kent S ; Widiyanto, Indra ; Xi, Chen ; Guoliang, Li ; Ming, su ; Yang, huang ; Yang, Li ; Kloss, Maike ; Schwegmann, Heike ; Lee, Mi-Kyung ; et al.
Linked to the ASEM III in Seoul, Korea, 20 - 21 October 2000, openend to students from fine arts schools selected in ASEM countries.
kunstcatalogus